Nanosponge Gel: A novel therapeutic approach for Rheumatoid Arthritis Treatment - Dr.P Premkumar; Nikhila. M. Nair; Jency Abraham (The Bioscan, 2025)
Nanotechnology and nanomedicines being vast research field offers solutions to many unresolved problems of drug delivery and therapeutics and is an expanding branch of science. Among the available nanoparticles based dosage forms, nanosponges (NS) vanquish the lead because it solubilizes poorly water soluble drugs and prolongs the release of drugs. Nanosponges are very tiny, nanoscopic, sponge-like particles, that consists of a number of cavities filled with medications. Nanosponges have gained attention due to its distinctive characteristics to improve medication delivery systems among the several alternatives. Rheumatoid Arthritis is an autoimmune disease and causes inflammation in the affected parts of the body. Nanosponge gel will be potentially useful for the treatment of Rheumatoid Arthritis. It ensures controlled and prolonged drug release and a good stability. The aqueous solubility of nanosponges allows them to be used efficiently for medications having low solubility. Nanosponges can also act as a vehicle for enzymes, proteins, vaccines and antibodies. The targeting of drug delivery systems by nanosponges is available as a topical administration. The porous shape of nanosponges gives a distinct capacity to entrap medicament and side by side provides the desired release rate. On topical administration it penetrates at the site of action and binds to the receptor site and release the drug in a desirable and predictable manner. The ingredients used, methods of preparation, its characterization, applications as drug delivery system in the field of nanotechnology world are presented in this paper.